Case report: Blood purification effectively relieves multiple system failure in patient with rabies - Daibin Kuang; Ming Luo; Jiabao Chen; Congmin Liang; Ziwei Cai; Zeqiang Yuan; Zhuandi Zhou; Jialong Chen; Chunlai Fu (Frontiers Media S.A., 2022)
Rabies is an infectious disease of animal origin with a high mortality rate. In the early stages of rabies, the rabies virus (RABV) is usually undetectable in saliva and cerebrospinal fluid (CSF). In addition, there are still no effective drugs and treatments. Here, we present a case in which blood purification alleviated multisystem failures. The patient was a 45-year-old woman who presented with the fear of water and wind, restlessness, and hyperactivity. RABV was detected in her saliva by high-throughput sequencing Next Generation Sequencing (NGS) and polymerase chain reaction (PCR). Based on typical clinical symptoms and the result of NGS and PCR, the patient was diagnosed as a confirmed case of rabies. Hemodialysis combined with antiviral therapy and intensive care unit (ICU) treatment can effectively relieve circulatory failure, respiratory failure, and renal failure. Finally, she died of brain death on the 34th day of admission. The case report showed that blood purification was positive for rabies-induced organ failure. Blood purification combined with antiviral therapy can prolong the lives of patients with rabies to some extent.